Perceived Push–Pull Factors Influencing Revenge Travel to Bataan Province - Joseph O. Cipriano; Rolando R. Calma; Mario Alex S. J. Clarin; Luisito V. Correa, Jr.; Ken Paul M. Espinosa (Future Science / FSH-PH Publications, 2026)
The study aimed to explore and quantify the push-pull factors that contributed to the tourists' choice of travel destinations in Bataan Province, Philippines as a form of revenge travel, utilizing the descriptive-quantitative research method. A total of 400 local and domestic tourists aged 18 to 65 who visited and stayed in any of the five (5) municipalities—Balanga, Pilar, Bagac, Mariveles, and Morong—in Bataan Province served as respondents. The study revealed that push factors influencing travel to Bataan Province included novelty seeking, ego enhancement, and the desire for rest and relaxation, as respondents were motivated by new experiences, family bonding, and personal enjoyment. Pull factors likewise played a crucial role, with environment and safety, as well as cultural and historical attractions, being highly prioritized by respondents. The affordability and quality of tourism facilities further enhanced the satisfaction of their travel needs. In general, the study revealed that push and pull factors were both significant in helping respondents in choosing their travel destination in Bataan Province. Additionally, the results revealed that there was a significant difference in the influence of push and pull factors when the demographic profile of the respondents was considered. Based on the study’s findings, to enhance Bataan’s cultural tourism appeal, stakeholders should develop diversified cultural programs that highlight the province’s heritage and ecology, prioritize sustainability and community collaboration, and deliver high-quality, data-driven tourism experiences aligned with tourists’ diverse motivations.